Tri-ponderal mass index and left ventricular hypertrophy in a cohort of caucasian children and adolescents with obesity - Sara Vizzuso; Alberico Del Torto; Giulia Fiore; Stefano Carugo; Gianvincenzo Zuccotti; Elvira Verduci (BMC, 2024)
Abstract Background Pediatric obesity is a global emerging burden for society; among its health-related consequences there are hypertension (HTN) and left ventricular hypertrophy (LVH). Several anthropometric indices have been investigated for the early identification of cardiovascular risk in children. The aim of the present study was to assess whether tri-ponderal mass index (TMI) was associated with LVH in a cohort of Caucasian children and adolescents with obesity. Methods In this observational study, 63 children and adolescents with obesity aged 7-to-16 years were enrolled. During outpatient visits, adiposity, and cardio-metabolic indices (BMI z-score, WHR, TMI, ABSI) were collected. All subjects underwent a 24-hour ambulatory blood pressure monitoring (ABPM) and transthoracic echocardiography. Results Children and adolescents with obesity with LVH had significantly higher BMI z-score (p = 0.009), WHR (p = 0.006) and TMI (p = 0.026) compared to children without LVH. WC and WHR were the only indices significantly associated with left ventricular mass index (LVMI). Conclusion Left ventricular remodeling is associated with the cardio-metabolic risk markers WC and WHR, but not with the adiposity index TMI among children with obesity.